Anesthetic management in hypoplastic left heart syndrome: A case report - Huamán-Robles, Marina (2022)
Background: Hypoplastic left heart syndrome may appear with clinical signs immediately at birth, being responsible for neonatal deaths within the first week of life. Clinical recognition and echocardiographic findings are key to timely diagnosis and treatment. Case report: describes the anesthetic procedure of a neonate with hemodynamic instability who required emergency surgery for bilateral pulmonary banding to maintain the balance between pulmonary and near-unit systemic flow ratio, along with mechanical ventilation maneuvers, anesthetic, inotropic and adjuvant drugs to control vascular resistance and blood flow, thus achieving hemodynamic stability of the patient, which allowed him to undergo an elective Norwood Sano procedure on the fifth day, and which was tolerated with extubation 15 days after surgery. Conclusion: The right timing of the surgical indication increases the survival of patients with hypoplastic left heart syndrome.